2021
DOI: 10.3390/jcm10112324
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Snail-1 in Thyroid Cancer—What We Know So Far

Abstract: Thyroid carcinomas, despite the usually indolent behaviour and relatively good overall prognosis, show a high tendency to gain invasive phenotype and metastasise in some cases. However, due to a relatively slow progression, the exact mechanisms governing the metastatic process of thyroid carcinomas, including the epithelial-to-mesenchymal transition (EMT), are poorly described. One of the best-known regulators of cancer invasiveness is Snail-1—a zinc-finger transcription factor that plays a key role as an EMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 97 publications
1
1
0
1
Order By: Relevance
“…Finally, the multivariate analysis demonstrated that none of the molecular parameters analyzed represented an independent prognostic factor for DFI. In agreement with our previous observations, in this analysis, only lymph node metastasis was capable of a significant prediction of the DFI both in our case study and that of the TGCA network, with a hazard ratio, respectively, of 21.0 and 5.8 [ 54 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the multivariate analysis demonstrated that none of the molecular parameters analyzed represented an independent prognostic factor for DFI. In agreement with our previous observations, in this analysis, only lymph node metastasis was capable of a significant prediction of the DFI both in our case study and that of the TGCA network, with a hazard ratio, respectively, of 21.0 and 5.8 [ 54 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous work has demonstrated that the NF- κ B subunit, p-65, binds to the Snail promoter and directly upregulates the expression, resulting in the repression of E-cadherin expression [ 33 , 34 ]. Snail downregulated the expression of other epithelial molecules and induced the expression of genes associated with a mesenchymal and invasive cell phenotype [ 35 ]. Furthermore, the fibrotic marker CTGF was identified as a downstream target of Snail.…”
Section: Discussionmentioning
confidence: 99%
“…Las CSC pueden experimentar TEM para adquirir características mesenquimales y contribuir a la invasión y metástasis La TEM es un proceso biológico que puede ocurrir durante el desarrollo embrionario, la cicatrización de heridas y la progresión tumoral mejor caracterización de este factor de transcripción podría tener implicancia pronosticas para el CT 22 .…”
Section: Contexto Biológicounclassified